Aquaculture of marine ornamental fish: overview of the production trends and the role of academia in research progress. (27th August 2019) - Pouil, Simon; Tlusty, Michael F.; Rhyne, Andrew L.; Metian, Marc
Abstract: The marine ornamental fish trade is expanding and still largely relies on wild fish from tropical coral reef ecosystems. There are unknowns in the wild harvest so that the sustainability of marine ornamental fish trade can therefore be questioned with aquaculture being perceived as a responsible alternative for the procurement of these ornamental marine fish. However, there are still many technical constraints that hinder its development. These blocks require additional coordination with the outcome being an accelerated development of ornamental marine fish production. The main objective of this review was to better identify, understand and discuss the role and the impacts of academic research in the production of marine ornamental fish through qualitative and quantitative approaches. To do so, 222 selected scientific publications (including peer‐reviewed articles, conferences articles, thesis and reports) from the literature available to date were analysed and outcomes were framed in perspective of the total number of captive‐bred species. Results of the meta‐analyses indicate that academic research has led to significant advances in the breeding of some of the more difficult to breed species. While it has a leading role in conservation, its advance of techniques still lags behind private companies and hobbyists. Partnerships promoting synergistic activities between academic research institutes and the private sector (aquaculture farms and public aquariums) are important to optimize future ornamental marine fish production.